An Analysis Of Language Variation Of The Interaction Speech By Sellers And Buyers At “Pasar Kamis” In Pulau Aro Village Tabir Ulu District (Sociolinguistics Analysis) - Rahayu, Siti; Magria, Vera; Efendi, Dedi (Krinok:Jurnal Linguistik Budaya, 2024)
This research analyzes language variations used in buyer and seller transaction interactions in traditional markets in Jambi Province, Merangin Regency, Tabir Ulu District, precisely in Pulau Aro village. The benefits of this research include: (1) to identify the kinds based on user of language variations used in buyer and seller interactions at the traditional market called Pasar Kamis in Pulau Aro Village, Tabir Ulu District, Merangin Regency. Jambi Province. Then the data was analyzed using the Referential method and use formal and informal techniques to present research results. Data sources are brought directly from the location by recording and recording video with accurate data evidence.  The collected data was analyzed based on  kinds base on user of language variations in traditional markets, namely “Pasar Kamis” Market in Pulau Aro Village. The percentage of the language variations that occur between seller and buyer transactions are analysed in this thesis. The total of collected data is 21 data, which is categorized into 15 data of regional variations,1 data of social variations 5 data of social dialect.